Kecerdasan Emosi dan Dukungan Sosial terhadap Kesiapan Ibu dalam Mengatasi Kecemasan Melahirkan Anak - Mita Fani Tri Mutya (Psyche 165 Journal, 2022)
Anxiety conditions in pregnant women with their first child are very important to consider in the face of birth. Anxiety is strongly influenced by internal and external factors. This study aims to determine the role of emotional intelligence, social support and age on anxiety. The method used in this study is a quantitative method for 71 pregnant women with their first child. Pregnant women studied were found at Awalbros Hospital in Pekanbaru City. Gestational age ranges from 27 to 40 weeks. The measuring instrument used in this research is the emotional intelligence, social support and anxiety scale variables. The study also involved a control variable, namely the age of pregnant women. The data was processed using regression analysis with the help of Personal Computer (PC) and Statistical Product and Service Solutions (SPPS) software version 16.00 for windows. The results showed that emotional intelligence and social support played a positive and significant role on anxiety with the F value being 23,542 and p being 0.001 (p<0.05); emotional intelligence and social support as well as age as control variables have a positive and significant role on anxiety with F value is 18,883 and p is 0,001 (p<0,05); the contribution of the predictor variables together is 45.8% to the criterion variable; and the contribution of the control variable to anxiety is 4.9%. Research is very helpful for pregnant women with their first child in following up on the effect of anxiety on emotional intelligence and social support. So this research is very helpful for pregnant women with their first child in facing birth.